Education Driving the Rise in Dutch Female Employment: Explanations for the Increase in Part-time Work and Female Employment in the Netherlands, Contrasted with Germany - Ronald Schettkat; Lara Yocarini (Institute for the Study of Labor (IZA), 2001)
Over the last 15 years, the Netherlands has experienced a tremendous jobs boom, mainly in services and female employment. This has often been related to changes in the Dutch institutional environment. Using a model which allows for direct utility of work, we find that institutional arrangements like the tax and pension system – often cited as a cause of the Dutch employment boom - contributed only marginally, if at all, to the rise in female labor supply. The increasing proportion of women with higher education and a high valuation of market work were the two main causes of rising female participation in the labor force. In addition, greater flexibility in work schedules (part-time work) has relaxed a demand constraint, allowing more women to participate in the labor market. We find: - that the increased number of women with higher education has contributed substantially to the rise in female labor force participation; - that it was only in the 1990s that the "behavioral" component contributed as much to rising female labor force participation as the "structural" (educational) component; - that there is no evidence that institutional specifics or the change in institutional arrangements (taxes and pensions) favored female labor force participation or that they provided strong incentives for part-time work; - that the work orientation of Dutch women is stronger than that of German women but that there is no evidence of a substantial increase in work orientation during the 1990s; - that there is no evidence that women were previously demand-constrained in the sense that they desired to work part-time but were prevented by a scarcity of part-time work.
Keywords: E24; J22; J16; J21; J24; 330; Employment; economics of gender; employment structure; time allocation and labor supply; demand for labor; human capital; Frauenerwerbstätigkeit; Arbeitsangebot; Bildungsniveau; Humankapital; Teilzeitarbeit; Beschäftigungseffekt; Schätzung; Niederlande